PENERAPAN METODE CERAMAH TIPE EKSTEMPORAN PADA MATA PELAJARAN AGAMA ISLAM DI SMP MUHAMMADIYAH 47 SUNGGAL - Hasibuan, Sukron; Fanreza, Robie (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2024)
The use of learning methods is currently one of the common problems among educational institutions, not only about how to use learning methods but also about the methods used in learning, but currently teachers and students often experience difficulties in learning, the use of learning methods comes in various types. extemporaneous and other types. The role of this extemporaneous learning method must be to be able to solve problems experienced by teachers and students. How Islamic religious education actually becomes an example of the use of learning methods, therefore, this approach has good benefits for learning carried out by Islamic religious education teachers. The method of implementing an extemporaneous lecture style is the focus of this investigation. Researchers in this qualitative research examined the extemporaneous lecture style carried out by Islamic religious education teachers at SMP Muhammadiyah 47 Sunggal. Researchers conduct interviews, observe phenomena, and document findings to fill knowledge gaps. Using Melles and Huberman to check if the data is valid. The results obtained show that the application of the extemporaneous type of lecture method in Islamic religious lessons is very effective and efficient in the success of the Islamic religious learning process. First, because it doesn't require a lot of instruments and teaching tools, so it seems simple. Second, many students or pupils can participate. Third, it is efficient in terms of time because what is needed is good mastery of the material.